Base‐Promoted Formation of an Annelated Pyrrolo‐1, 4‐oxazine Ensemble from 1H‐pyrrol‐2‐ylmethanol and Propargyl Chloride: A Theoretical and Experimental Study. Issue 1 (18th November 2019) - Vitkovskaya, Nadezhda M.; Bobkov, Alexander S.; Kuznetsova, Svetlana V.; Shcherbakova, Victoriya S.; Ivanov, Andrey V.
Abstract: Invited for this month's cover is the group of Prof. Dr. Nadezhda M. Vitkovskaya at Irkutsk State University and the group of Dr. Andrey V. Ivanov at the A. E. Favorsky Irkutsk Institute of Chemistry, Russian Federation. The image shows that three different pyrrole derivatives can be obtained from the same starting reagents. The reaction is easily controlled by the ratio of the reagents, the amount of alkali, and the degree of dilution. The three strings of the balalaika (a Russian folk instrument) that represent these parameters can produce melodies from the same notes symbolizing the reagents. The sheets with quantum‐chemical calculations under the musical notebook symbolize that the experimental work is based on the theoretical investigations. Read the full text of the article at 10.1002/cplu.201900407 . Abstract : "The work presented is a continuation of a series of investigations to activate several reactive centers of pyrrole with the aim to synthesize previously unknown compounds with promising properties, such as drugs and precursors of materials with target characteristics. The synthesis is transition‐metal‐free and affords high yields and selectivity of the products." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.201900407 ).